Implementation of Ki Hadjar Dewantara's Educational Philosophy Through Differentiated Learning In Pancasila and Civic Education for Junior High School Level - Septiwiharti, Dwi; Kulyawan, Roy; Dewi, Anjar Kusuma; Imran, Imran (LPPM Universitas PGRI Sumatera Barat, 2025)
The article discusses Indonesia's education system and its implementation of the